Predicting attendance of post-treatment cancer care patients in general practice: the role of concomitant health conditions in the theory of planned behaviour - Ngune, Irene; Jiwa, Moyez; McManus, Alexandra; Hughes, Jeff; Parsons, Richard; Hodder, R. (WILEY-BLACKWELL, 2014)
Background: There is mounting emphasis to transfer follow-up care of cancer patients to general practice due to the increasing number of patients at hospital cancer clinics. Uptake of this approach is rather slow despite rigorous research work done in this field. Issues that affect endorsement of this approach have not been fully determined and, in particular, patient factors that may affect uptake of this programme have not been explored. Objective: To examine the role of comorbidities in the theory of planned behaviour (TPB) in influencing patients’ intention to attend follow-up visits with a general practitioner (GP). Methods: A self-administered questionnaire was developed based on the TPB to assess colorectal cancer (CRC) patients’ intention to attend follow-up visits with a GP. Results: Sixty-six patients participated in the study. All factors [attitude, subjective norms and perceived behaviour control (PBC)] accounted for 43.3% of the variance on future follow-up visits. Attitude explained 23.3% of the variance, but PBC and subjective norms did not account for any significant variance on future intention to attend a follow-up visit. Univariate analysis suggested that attitude and the presence of a coexisting chronic illness significantly affected future intention to visit a GP (attitude: R2 = 0.233, F [1, 65] = 4.345, p < 0.01; comorbidity: R2 = 0.128, F [1, 65] = 3.019, p < 0.05). Conclusion: Two factors, CRC patients’ attitude and having a coexisting chronic illness, had the greatest influence on their intention to seek advice from a GP post treatment. By triaging patients with existing concomitant illnesses and improving patients’ knowledge on what CRC issues GPs can address, more CRC survivors may seek medical advice from a GP.